Extreme measures. (Economist, 2000)
Part of a special section on technological innovation. “Extreme programming” (XP), a software design approach advocating that more method equals less confusion, is growing in popularity. XP was developed in 1996, when software developer Kent Beck was asked by car maker Chrysler to save a project that it had scrapped. For this project, Beck designed a set of directions to keep code “elegantly written.” However, some of these rules have generated controversy, particularly the one that specifies that programmers work in pairs, on one terminal, on each bit of code. Critics argue that this rule will lead to inefficiency, with the pairing of programmers with mismatched capabilities. Nonetheless, proponents of XP believe that with the rotation of people to different tasks and pair-programming there is the benefit of having an easy-to-maintain code, with minimum expense, after only a few years.